The Implementation of Technology Integration During Distance Learning in the Graduate Program of Universitas Negeri Makassar - Syahrullah, Syahrullah; Dollah, Syarifuddin; Weda, Sukardi (Celebes Journal of Language Studies, 2023)
This study aims (1) to investigate the implementation of technology integration in distance learning, (2) to discover students’ perception of the implemented technologies, and also (3) to reveal students’ motivation toward the implemented technologies during distance learning. The study is descriptive research that used a mixed-methods approach using a questionnaire survey and interviews in collecting the data. The subject of this study was lecturers and 60 students of the academic year 2021/2022 of English Education, Graduate Program of Universitas Negeri Makassar. The results of the study are; (1) technologies that had been integrated into the graduate program during distance learning were Zoom, SYAM-OK, WhatsApp, and Google Meet. The technology integration was successful with common problems such as connection issues and minimal support from the university. Furthermore, (2) the student’s perception of accepting this technology based on the Technology Acceptance Model (TAM) showed positive perception, which the average overall score of those four applications being 74.1%. In detail, SYAM-OK had a positive perception (70%), Zoom had a positive perception (81.5%), Google Meet had a moderate perception (63.5%), and WhatsApp had a positive perception (81.25%). Additionally, (3) the analysis of student motivation indicated that the students had a positive level of motivation during the integration of technology in distance learning. The average percentage score was 74.5%, with Attention (70%), Relevance (74%), Confidence (78%), and Satisfaction (76%). All aspects were classified as high motivation. Overall, this study highlights the importance of integrating technology in distance learning to improve student motivation and enhance the learning experience.